(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the onomastic characteristics of occupational terms in the Uzbek language. It identifies how professions influence personal and place names and examines their cultural and historical relevance. The study also addresses the stylistic devices and sociolinguistic implications associated with occupational terms in Uzbek onomastics.